Product Quality and Social Media Virality as Predictors of Consumer Purchase Decisions in Culinary SMEs - Darajat, Zidna Zakia; Mustapita, Arini Fitria; Athia, Ita (LPPM Universitas Jambi, 2026)
This study investigates how product quality, social media marketing, and word-of-mouth influence consumer purchase decisions among small culinary businesses in Malang, Indonesia. The research employed a quantitative explanatory design with purposive sampling. A total of 120 respondents were selected based on three criteria: being at least 17 years old, having purchased from small culinary enterprises within the previous six months, and having received information about the businesses through social media or personal recommendations. Data were gathered using a structured questionnaire measured on a five-point Likert scale. Multiple linear regression was used to analyze the data after conducting validity and reliability assessments as well as classical assumption tests. Hypotheses were tested through t-tests to examine partial effects and an F-test to assess simultaneous effects. The results indicate that product quality, social media marketing, and word-of-mouth each have a positive and statistically significant impact on purchase decisions. Social media marketing was identified as the strongest predictor, followed by product quality and word-of-mouth. Together, these variables accounted for 62.9% of the variance in purchase decisions, demonstrating substantial explanatory power.The findings highlight the importance of maintaining product consistency, implementing engaging social media strategies, and encouraging positive customer recommendations. Future studies are encouraged to include broader samples, additional variables such as price and service quality, and alternative analytical techniques to enhance generalizability.